1986
DOI: 10.1073/pnas.83.13.4859
|View full text |Cite
|
Sign up to set email alerts
|

Human alpha-galactosidase A: nucleotide sequence of a cDNA clone encoding the mature enzyme.

Abstract: The complete nucleotide sequence has been determined for a Kgtll cDNA done (XAG18) containing the full-length coding region for the mature lysosomal form of human a-galactosidase A (a-Gal A; EC 3.2.1.22). The XAG18 insert contained a 1226-base-pair sequence with an open reading frame encoding 398 amino acids of the mature polypeptide (predicted Mr = 45,356) and the last 5 amino acids of the propeptide sequence. The poly(A) signals AATACA and ATTAAA occurred 28 and 11 nucleotides prior to the TAA stop codon, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0
2

Year Published

1991
1991
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(97 citation statements)
references
References 32 publications
(34 reference statements)
0
95
0
2
Order By: Relevance
“…Since cDNA of a-GalA was cloned and characterized (Calhoun et aL, 1985;Bishop et aL, 1986), molecular abnormalities in more than one hundred families with Fabry disease have been studied. Bernstein et al (1989) reported that partial gene deletions were seen only seven families out of 130 families by Southern blotting analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since cDNA of a-GalA was cloned and characterized (Calhoun et aL, 1985;Bishop et aL, 1986), molecular abnormalities in more than one hundred families with Fabry disease have been studied. Bernstein et al (1989) reported that partial gene deletions were seen only seven families out of 130 families by Southern blotting analysis.…”
Section: Discussionmentioning
confidence: 99%
“…1. These primers were designed on the basis of the reported sequence data (Bishop et al, 1986;Kornreich et al, 1989).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The isolation and sequencing of the full-length cDNA and entire 12-kb genomic sequence encoding α-Gal A (Bishop et al 1986;Kornreich et al 1989) has facilitated characterization of the mutations causing Fabry disease. To date, a variety of mutations have been identified, including missense, nonsense, and splice-site mutations, as well as partial gene rearrangements, small deletions, and insertions, e.g., by (see also the Human Gene Mutation Database http:// archive.…”
Section: Introductionmentioning
confidence: 99%